2017
DOI: 10.1007/s11892-017-0877-0
|View full text |Cite
|
Sign up to set email alerts
|

Islet Microencapsulation: Strategies and Clinical Status in Diabetes

Abstract: Microencapsulation can play a significant role in overcoming the need for immunosuppression and lack of donor islet cells. This review focuses on microencapsulation and the clinical status of the technology in combating T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 61 publications
0
28
0
5
Order By: Relevance
“…The encapsulation of islets within a semipermeable material has thus emerged as an encouraging platform to eliminate the need for immunosuppression . Numerous successful preclinical studies have been reported for islets encapsulated in hydrogel microcapsules and macroscopic devices . Nonetheless, translational limitations remain for both approaches.…”
mentioning
confidence: 99%
“…The encapsulation of islets within a semipermeable material has thus emerged as an encouraging platform to eliminate the need for immunosuppression . Numerous successful preclinical studies have been reported for islets encapsulated in hydrogel microcapsules and macroscopic devices . Nonetheless, translational limitations remain for both approaches.…”
mentioning
confidence: 99%
“…Diğer çalışmalarda mikroenkapsülasyon tekniğinin hali hazırda kullanımda olduğu ancak özellikle ilaç salınımı gibi süreçlerde yeterli doz oranlarının ve kapsül özelliklerinin düzenlenmesi gerektiğinden bahsedilmektedir 22 . Mikroenkapsülasyon tekniğinin insan sağlığını doğrudan ilgilendiren bir diğer kullanım alanı, bir otoimmün hastalık olan ve Langerhans adacıklarında bulunan β hücrelerinin hasarı sonucunda glisemik kontrolün bozulduğu Tip 1DM hastalığının tedavisidir 13,23,24 . DM tedavisinde, özellikle odaklanılan araştırma alanı pankreastaki β hücrelerinin mikroenkapsüle edilerek hastaya verilmesidir.…”
Section: Discussionunclassified
“…DM tedavisinde, özellikle odaklanılan araştırma alanı pankreastaki β hücrelerinin mikroenkapsüle edilerek hastaya verilmesidir. Bu çalışmalarda da henüz optimize bir kapsülasyon yöntemi ve uzun dönemli klinik izlem parametreleri mevcut değildir 24 . Ancak yine de teknik farklı şekillerde değerlendirilerek görece başarılı sonuçlar elde edilmektedir.…”
Section: Discussionunclassified
“…Open macroporous encapsulation devices that allow revascularization of islets have demonstrated some promise but it still takes at least 7-14 days until a new functional vasculature is established in transplanted islets [3] and immunosuppressants are always required. Macro-and microencapsulation of islets and beta cells are an alternative to open devices that introduce a physical barrier to protect the transplanted islets from the host's immune system, potentially circumventing the need for immunosuppressive therapy [4] and mitigating some risks by protecting the patient from rogue cells in case of induced pluripotent-or embryonic stem cell-derived beta cell therapy [5][6][7][8][9][10][11]. Whatever the strategy chosen, the clinical success of encapsulation devices is hampered by a number of complex factors such as acute and long-term ischemia, limited vascularization and mass transport of crucial nutrients such as oxygen and insulin, and suboptimal biomaterial properties [12].…”
Section: Introductionmentioning
confidence: 99%